Outpatient initiation of long‐term continuous positive airway pressure in children. Issue 10 (1st August 2018) - Amaddeo, Alessandro; Frapin, Annick; Touil, Samira; Khirani, Sonia; Griffon, Lucie; Fauroux, Brigitte
Abstract: Introduction: Current guidelines recommend initiating continuous positive airway pressure (CPAP) in children during an overnight in‐hospital titration study. Due to a shortage of hospital beds and economic constraints, we started a program for outpatient initiation of CPAP in selected children with obstructive sleep apnea (OSA). Methods: Objective CPAP compliance and efficacy were evaluated in consecutive children enrolled in an outpatient CPAP program when they fulfilled the following criteria: persistent OSA, age >6 months, stable condition, family living in the Parisian area and agreeing with a regular follow‐up. Results: Thirty‐one children, median (range) age 8.9 years (0.8‐17.5), were included in the program. The most common diagnosis were Down syndrome ( n = 7), achondroplasia ( n = 3), and obesity ( n = 3). Median baseline obstructive apnea‐hypopnea index (OAHI) was 12.5 events/h (5‐100). Median duration of follow‐up was 12.3 months (2.2‐25.2). Four subjects (three adolescents with Down syndrome) were not compliant at 2‐month follow‐up with a compliance <4 h/night. In the other 27 subjects, median compliance was 08:21 h:min/night (05:45‐12:20), with a median number of night use per month of 25 (18‐30). CPAP efficacy at the end of follow‐up was excellent in the compliant subjects with a median AHI of two events/h (0‐4) and normal gas exchange with CPAP therapy. Three subjects were successfully weaned from CPAP treatment during the study period. Conclusion: Initiating CPAP in an outpatient setting in children is feasible and effective in selected subjects. A high rate of compliance can be achieved as well as a correction of OSA.